PJMHS 2021
DOI: 10.53350/pjmhs211592789
|View full text |Cite
|
Sign up to set email alerts
|

ICU Stay and Mortality Between Vaccinated and Non-Vaccinated Patients of Covid-19; A comparative Study

Abstract: Objective: The aim of this study is to compare the ICU stay and mortality in vaccinated and non-vaccinated covid-19 patients. Study Design: A Retrospective/ Comparative study Place and Duration: The study was conducted in Medicine department of Fauji Foundation Hospital Rawalpindi, duration of six months from October 2020 to March 2021. Methods: Total 120 patients of both genders had coronavirus disease were presented in this study. Patients were aged between 22-80 years. Demographical details of patients incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…It was revealed that COVID-19 vaccination was successful and beneficial for lowering the severity of the condition. Similar results were reported elsewhere wherein recovery among the vaccinated mass was greater (80%) than in non-vaccinated patients (38.6%) [ 35 ]. In contrast to vaccinated patients, who experienced hospitalization ICU admission and mortality was found in a smaller number of cases, the recurrence of poor consequences in non-vaccinated patients was significantly higher.…”
Section: Reviewsupporting
confidence: 91%
“…It was revealed that COVID-19 vaccination was successful and beneficial for lowering the severity of the condition. Similar results were reported elsewhere wherein recovery among the vaccinated mass was greater (80%) than in non-vaccinated patients (38.6%) [ 35 ]. In contrast to vaccinated patients, who experienced hospitalization ICU admission and mortality was found in a smaller number of cases, the recurrence of poor consequences in non-vaccinated patients was significantly higher.…”
Section: Reviewsupporting
confidence: 91%
“…A total of 14 studies were included to analyze the effect of age. We found no statistical difference in the age of the two groups (SMD = 0.085, 95% CI = À0.073-0.189, p = 0.388, 12 Case-control study 346 1100 ☆☆☆ ☆☆ ☆☆ 7☆ Wi 18 Case-control study 142 20 ☆☆ ☆☆ ☆☆ 6☆ Tenforde 13 Case-control study 314 1669 ☆☆☆ ☆☆ ☆☆ 7☆ Hsu 19 Case-control study 85 85 ☆☆ ☆☆ ☆☆☆ 7☆ Blanquart 20 Case-control study 724 5459 ☆☆☆ ☆☆ ☆☆ 7☆ Bollineni 21 Case-control study 14 56 ☆ ☆☆ ☆☆☆ 6☆ Marincu 22 Case-control study 62 62 ☆☆ ☆☆ ☆☆☆ 7☆ Wolff 23 Case-control study 260 507 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kalligeros 24 Case-control study 91 824 ☆☆☆ ☆☆ ☆☆☆ 8☆ Fragoulis 25 Cohort study 101 60 ☆☆☆ ☆☆ ☆☆☆ 8☆ Trunfio 26 Cohort study 55 110 ☆☆☆ ☆☆ ☆☆ 7☆ Safdar 27 Cohort study 45 65 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bouton 28 Cohort study 96 329 ☆☆ ☆☆ ☆☆☆ 7☆ Bosch 29 Case-control study 126 839 ☆☆ ☆☆ ☆☆☆ 7☆ Christensen 30 Case-control study 3346 13,619 ☆☆☆ ☆☆ ☆☆☆ 8☆ Yu 31 Case-control study 23 50 ☆☆☆ ☆☆ ☆☆☆ 8☆ Bayhan 32 Case-control study 38 190 ☆☆☆ ☆☆ ☆☆☆ 8☆ Kustin 33 Case-control study 396 396 ☆☆ ☆☆ ☆☆ 6☆ Toda 34 Case-control study 11 15 ☆☆☆ ☆☆ ☆☆☆ 8☆ Tian 4 Case-control study 88 41 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sayed 35 Case-control study 50 70 ☆☆☆ ☆☆ ☆☆☆ 8☆ Lee 36 Case-control study 174 587 ☆☆☆ ☆☆ ☆☆☆ 8☆ Luo 37 Case-control study 484 1782 ☆☆☆ ☆☆ ☆☆ 7☆ Puhach 38 Case-control study 139 245 ☆☆ ☆☆ ☆☆ 6☆ Whittaker 39 Case-control study 716 2487 ☆☆☆ ☆☆ ☆☆☆ 8☆ Sanghavi 40 Case-control study 149 478 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (1) 41 Case-control study 250 250 ☆☆☆ ☆☆ ☆☆☆ 8☆ Butt (2) 42 Case-control study 456 456 ☆☆☆ ☆☆ ☆☆☆ 8☆ Spiera 43 Case-control study 88 2317 ☆☆ ☆☆ ☆☆☆ 7☆ Baltas 44 Case-control study 119 476 ☆☆☆ ☆☆ ☆☆ 7☆ John 45 Case-control study 254 508 ☆☆ ☆☆ ☆☆ 6☆ Jacobson 46 Case-control study 189 471 ☆☆ ☆☆ ☆☆ 6☆ Estofolete …”
Section: Ageunclassified